Plan de negocio para la elaboración y distribución de ponche suizo con gelatina dietética en la ciudad de Quito - Molina Vasco, Joan José (2019)
The business plan that gives rise to the development of this research focuses on a Swiss punch with dietary gelatin that will be commercialized on an island in the commercial center located north of the Metropolitan District of Quito. Because currently in the society there has been a trend towards healthy eating, this diet dessert is aimed at all those people motivated to care for their health and that being a novel product can have a great impact on the food market, generating an opportunity for the project. In addition, due to the existence of several spaces within the shopping centers, there will be no difficulty in signing a concession contract in order to implement the business idea on a commercial island. An integral analysis of the client was carried out, for which quantitative tools (surveys to potential consumers) and qualitative tools (interviews to experts and focus group) were used to determine how feasible it is to implement a dietetic dessert in the CCI shopping center. The name of the commercial island is "Nutritional Dessert" that encompasses a nutritional message, moving towards a healthy and reliable perspective for the client. Also, a marketing plan was developed, which included the target market, general strategy, value proposal and the marketing mix. All this marketing plan is completely detailed. Likewise, a financial plan was made detailing all the five-year projected financial statements, the capital structure, initial investment and financial indicators comparable to the indices of the industry in which the project belongs. Finally, when carrying out the financial evaluation, the viability and profitability of the project were determined in the long term, in addition to having a target market support in terms of market research, and that there are great opportunities for entrepreneurship.